The return of Brody McBride - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- McBrides, 2014)
Brody and Rain were an item until Roxy stepped in and stole Brody away. Soon after, he left for the Army. Eight years later, he has returned to town, hoping to mend the rift between him and Rain only to find that Rain is raising his two daughters, both hers and Roxy's. Can he step in and be a father and husband to this instant family or will Roxy be able to lure him way once again?